Characteristics of Islam - Shehu, Fatmir Mehdi (2022)
This paper seeks to introduce to the postgraduate students the main characteristics of Islam and how to make theme relevant to their time as well as field of specialization. Its goal is to create awareness among the postgraduate students about the characteristics of Islam and how to respond to contemporary ideologies, such as scientism, atheism, humanism, secularism, etc. The focus of this workshop paper is on the description of Islam as a comprehensive way of life and then discusses the Al-Rabbaniyyah (Divine Origin) Al-Shumul (Comprehensiveness), Al-Tawazun (Moderation/Balance), Al-Thubut Wa al-Murunah (Stability and Flexibility), Al-Waqiyyah (Realism/the Unity of Soul and Body); and Al-Alamiyyah (Universality).